Effect of AGE and Gamma-mangostin on Luteinizing Hormone Receptor (LHR) Levels in Leydig Cell Culture of Male Aging Rats: Preliminary Study - Dicky Moch Rizal; Muhammad Herdhana Ash Shidiqi; Rustamaji Rustamaji (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Advanced Glycation End Products (AGE) are proteins that can cause cell destruction by increasing oxidative stress and inflammation. This product resulted from a series of chemical reactions after an initial glycation reaction. A Leydig cell is one of the types of cells affected by AGE. This cell is located in the interstitial of the testes and stimulated by the luteinizing hormone. This study aimed to compare the luteinizing hormone receptor levels in Leydig cell culture of Sprague-Dawley rat induced by AGE only and the one that administered gamma-mangosteen. We conducted an experimental laboratory study on luteinizing hormone receptor levels in Leydig cell culture of Sprague-Dawley rats induced by advanced glycation end products 200 μg/mL and given gamma-mangostin 5 μM compared to the one that was not given gamma-mangostin. The highest mean of LHR level was in group 3 given gamma-mangostin 5 μM (8.06 pg/ cells/24h), and the lowest mean was in group 1 (control) (7.78 pg/ cells/24h). The LHR levels in the rats' Leydig cell culture given 5μM gamma-mangostin were higher than the other groups indicate the inhibition capacity on the oxidation process caused by AGE in aging rats Leydig cells culture.